Optimization Of Community Income During The Covid-19 Pandemic From Cooking Oil Waste Into Soap In Sukaratu - DENI Sunaryo (Society : Jurnal Pengabdian Masyarakat, 2022)
Sukaratu Village, Cikeusal has rapid population growth and culinary business development because there is the Serang Panimbang Section 1 toll gate which is an economic magnet. This has a positive impact on the community, but also has a negative impact on the environment. The negative impact of this culinary business is the high volume of used cooking oil (cooking) waste. This happens because people throw used cooking oil away. Waste cooking oil if not managed properly will make the environment dirty and can pollute water and soil. To overcome this problem, it is necessary to innovate in the management of used cooking oil by involving the community so that the waste can be used as a product of economic value. One of the potential waste cooking oil is the high content of fatty acids so that it can be used as an environmentally friendly dish soap. Therefore, community service activities were carried out to increase the added value of used cooking oil by processing it into dish soap. Skills training for processing used cooking oil into dish soap has been carried out for the community in Sukaratu Village, Cikeusal and provides benefits: 1) The community knows the negative impact of used cooking oil on health and the environment, 2) The community knows and is skilled at applying appropriate technology for processing used cooking oil into dish soap, 3) People know the economic potential of used cooking oil waste, 4) Encourage community empowerment.